2017
DOI: 10.1002/car.2496
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Parental Capacity when there are Concerns about an Unborn Child: Pre‐Birth Assessment Guidance and Practice in England

Abstract: Assessment where there are concerns that an unborn child is likely to suffer significant harm is one of the most difficult tasks that social workers undertake; the legal and ethical context makes the process of assessment and intervention during this period complex. This paper explores pre‐birth assessment guidance and practice in England. Local safeguarding guidance in 147 English localities was accessed and analysed, and interviews were conducted with 22 practitioners involved in pre‐birth assessments. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 7 publications
0
16
0
2
Order By: Relevance
“…Data revealed the fairly short timescales for pre‐birth assessments to be conducted and the need for practitioners to be non‐judgemental and honest in their attitudes and practices. The study also found that some interviewees ‘regarded pre‐birth assessments as less urgent than cases involving infants/older children, thereby increasing delays in decision‐making’ (Lushey et al ., , p. 97).…”
Section: Assessmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Data revealed the fairly short timescales for pre‐birth assessments to be conducted and the need for practitioners to be non‐judgemental and honest in their attitudes and practices. The study also found that some interviewees ‘regarded pre‐birth assessments as less urgent than cases involving infants/older children, thereby increasing delays in decision‐making’ (Lushey et al ., , p. 97).…”
Section: Assessmentmentioning
confidence: 95%
“…The first paper in this issue by Clare Lushey and colleagues () reports on a study which explored pre‐birth assessment guidance and practice in England. Pre‐birth assessment is undertaken when there are concerns that an unborn child is likely to suffer significant harm.…”
Section: Assessmentmentioning
confidence: 99%
“…Five studies examined the use of date and frameworks within child protection [93][94][95][96][97] , study characteristics are provided in Table 6 Two studies analysed routinely collected data. Data recorded about hospital admissions for children under 5 years old from 2007 to 2009 related to child maltreatment was analysed 93 .…”
Section: Use Of Data/frameworkmentioning
confidence: 99%
“…One study 97 investigated local safeguarding guidance on and social workers use of pre-birth assessments. The local guidance was generally more detailed than the national guidance but rarely considered legal and ethical issues.…”
Section: Use Of Data/frameworkmentioning
confidence: 99%
“…Most local authorities have built upon national statutory guidance by developing local protocols tailored to referrals involving unborn children, which contributes to variation in the quality of guidance and pre-birth child protection practice across England ( Lushey, Barlow, Rayns, & Ward, 2018 ). There is also an abundance of qualitative evidence suggesting many practitioners have insufficient guidance on these pre-birth procedures, resulting in delayed pre-birth assessments and missed opportunities for early intervention ( Honey, Miceli, & Mayes, 2019 ; Lushey et al, 2018 ; Mason, Robertson, & Broadhurst, 2019 ).…”
Section: Introductionmentioning
confidence: 99%